σ-Hole Interactions of Covalently-Bonded Nitrogen, Phosphorus and Arsenic: A Survey of Crystal Structures - Peter Politzer; Jane S. Murray; Goran V. Janjić; Snežana D. Zarić (Crystals, 2014)
Covalently-bonded atoms of Groups IV–VII tend to have anisotropic charge distributions, the electronic densities being less on the extensions of the bonds (σ-holes) than in the intervening regions. These σ-holes often give rise to positive electrostatic potentials through which the atom can interact attractively and highly directionally with negative sites (e.g., lone pairs, π electrons and anions), forming noncovalent complexes. For Group VII this is called “halogen bonding” and has been widely studied both computationally and experimentally. For Groups IV–VI, it is only since 2007 that positive σ-holes have been recognized as explaining many noncovalent interactions that have in some instances long been known experimentally. There is considerable experimental evidence for such interactions involving groups IV and VI, particularly in the form of surveys of crystal structures. However we have found less extensive evidence for Group V. Accordingly we have now conducted a survey of the Cambridge Structural Database for crystalline close contacts of trivalent nitrogen, phosphorus and arsenic with six different types of electronegative atoms in neighboring molecules. We have found numerous close contacts that fit the criteria for σ-hole interactions. Some of these are discussed in detail; in two instances, computed molecular electrostatic potentials are presented.